If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 1 = 7 + -1y Reorder the terms: 1 + y = 7 + -1y Solving 1 + y = 7 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 1 + y + y = 7 + -1y + y Combine like terms: y + y = 2y 1 + 2y = 7 + -1y + y Combine like terms: -1y + y = 0 1 + 2y = 7 + 0 1 + 2y = 7 Add '-1' to each side of the equation. 1 + -1 + 2y = 7 + -1 Combine like terms: 1 + -1 = 0 0 + 2y = 7 + -1 2y = 7 + -1 Combine like terms: 7 + -1 = 6 2y = 6 Divide each side by '2'. y = 3 Simplifying y = 3
| 5thirdsx-4thirdsx-1=8 | | 7b-75=6b-60 | | x*x-3x+1.5=0 | | 5x^4+x^3-1=0 | | 7(2x-2)=16 | | 7+6m=22+m | | y=x(-0.0125x+0.5) | | 2/5x-18=-14 | | 3y-8=y+4 | | 13u-11u+5=19 | | 4k+3=2k+17 | | 2(y-2)+y=5 | | 12=5x+5x+2 | | z-2z+-4=3 | | -6x^3-24=-6x^2-24x | | -n^2-6n-9=0 | | 5(x+7)-8x+12= | | 5a=a+20 | | 3(6m+1)=20 | | 4t=2t+14 | | -5y+14y=-18 | | 4x^(-2/3)=16 | | 11x=5-x | | -4(v-1)=-2v-16 | | 4x^-2/3=16 | | 2.50x+9.75y=36.50 | | ax^2=4x+7 | | 12y+11=49 | | 45x^2+25x^5+20x^2=0 | | 9/33=12/x | | 12s-5s=14 | | -4y+2=-5y-3 |